Evaluation of alpha-methylacyl-CoA racemase, metallothionein and prostate specific antigen as prostate cancer prognostic markers - Gumulec, J; Masarik, M; Krizkova, S; Hlavna, M; Babula, P; Hrabec, R; Rovny, A; Masarikova, M; Sochor, J; Adam, V; Eckschlager, T; Kizek, R (Neoplasma, 2012)
Current diagnostic techniques are inefficient in distinguishing latent and low-risk forms of prostate cancer from high-risk forms. The present study is focused on determination of putative tumor markers of aggressive high-grade forms of prostate cancer. Potential markers were determined in blood sera of 133 patients (82 cases and 51 controls) and in cell lines (Gleason score 9-derived 22Rv1 and normal tissue derived PNT1A) on mRNA and protein levels. Alpha-methylacyl-CoA racemase (AMACR), metallothionein classes 1A and 2A (MT1A and MT2A) were determined and compared to prostate specific antigen (PSA) levels. On mRNA level, significantly increased expression of MT2A (2.4-fold), PSA (2.6-fold) and AMACR (8.4-fold) and insignificantly (1.9-fold) elevated MT1A in 22Rv1 compared to non-tumor PNT1A were determined. On protein level, significant enhancement of free PSA and total PSA in tumor cell line was evident. AMACR protein was 1.5-fold elevated in tumor line (below the level of significance). Contrary to mRNA, significantly (p = 0.01) reduced level of MT protein in tumor lines was determined. In the case of serum level, significantly enhanced MT level (4.5-fold) in patients' sera was found. No significant changes were observed in the case of AMACR. These findings indicate possible alternative role of MT to PSA prostate cancer marker. In addition, level of AMACR is distinctly higher in the Gleason score 9 in serum of patients and MT shows a descending trend in relation to Gleason score.
Keywords: Prostatic Neoplasms; Adenocarcinoma; nádory prostaty; Humans; Case-Control Studies; messenger RNA; lidé středního věku; studie případů a kontrol; Biomarkers, Tumor; Racemases and Epimerases; Aged; dospělí; Blotting, Western; Prostate-Specific Antigen; senioři; lidé; Metallothionein; nádorové biomarkery; Adult; RNA, Messenger; Neoplasm Grading; Male; Middle Aged; racemasy a epimerasy; prostatický specifický antigen; prognóza; stupeň nádoru; Real-Time Polymerase Chain Reaction; Prognosis; adenokarcinom; metalothionein; western blotting; mužské pohlaví; kvantitativní polymerázová řetězová reakce